WOMEN'S POSITION AND RIGHT IN WAYNE WANG'S MAID IN MANHATTAN MOVIE (2002): A FEMINIST APPROACH - KARTIKASARI, ERNA DEWI (2011)
The major problem of this study is to reveal how women's position and right are reflected in Wayne Wang's Marisa Ventura. The objective of this study is to analyze the movie based on its structural elements and a feminist approach. In analysis, the writer uses qualitative method. The object of the study is Wayne Wang's Marisa Ventura released in 2002 in the United States. The data sources consist of primary and secondary data sources. The primary data source is Marisa Ventura movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the historical background of America in the late of twentieth century. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, Wayne Wang wants to describe that in order to get their rights as human being women should be smart and talented and women are expected not only to accept the condition and wait for the miracle but they must struggle to get freedom in all aspect of life. The second, this movie contains many facts that reflect woman's position, woman's role, woman's right, and woman's participation in leading her life as a maid.